2016
DOI: 10.4103/1319-2442.178549
|View full text |Cite
|
Sign up to set email alerts
|

Utility of saliva as a sample to assess renal function and estimated glomerular filtration rate

Abstract: Diagnosis of renal diseases by assessing renal parameters in saliva. Biochemical investigations using serum form important component of monitoring patients with renal disease. Utility of saliva, in diagnosis and monitoring of patients with renal disease and for calculation of estimated glomerular filtration rate (eGFR), was studied. Sixty patients with renal disease and sixty ageand sex-matched healthy controls were studied. Urea, creatinine, sodium, potassium, uric acid, calcium, and phosphorus were measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 1 publication
2
5
0
1
Order By: Relevance
“…Thus, salivary concentrations of creatinine and urea reflect plasma concentrations only in mice with substantially decreased renal functions. The results are consistent with previous studies showing that salivary creatinine and urea reflect their plasma levels only in patients with kidney diseases, but not in healthy controls [ 25 , 26 ]. Studies focusing on patients with CKD have shown that the analysis of saliva might be useful to diagnose or monitor CKD and to distinguish moderate stage from terminal stage renal failure [ 11 , 15 , 27 ].…”
Section: Discussionsupporting
confidence: 93%
“…Thus, salivary concentrations of creatinine and urea reflect plasma concentrations only in mice with substantially decreased renal functions. The results are consistent with previous studies showing that salivary creatinine and urea reflect their plasma levels only in patients with kidney diseases, but not in healthy controls [ 25 , 26 ]. Studies focusing on patients with CKD have shown that the analysis of saliva might be useful to diagnose or monitor CKD and to distinguish moderate stage from terminal stage renal failure [ 11 , 15 , 27 ].…”
Section: Discussionsupporting
confidence: 93%
“…The concentrations of salivary urea measured by this method were slightly lower than the corresponding serum urea concentrations (Table 1). This is consistent with several published reports in the literature (9,25,26), and, because saliva is an ultrafiltrate of blood, the same components measured in saliva might be expected to be lower than in blood (28). However, a few studies have reported levels of salivary urea that are similar to, or even higher than, serum urea in some patients with CKD (26,29).…”
Section: Discussionsupporting
confidence: 92%
“…A number of studies have shown that various salivary components, including urea, cortisol, creatinine, uric acid, and phosphate, correlate positively with the severity of CKD and are, therefore, potential indicators of renal function (5)(6)(7)(8). Of these, salivary urea has been particularly addressed because it correlates positively with elevated serum urea levels found in patients with CKD (9,10). Hence, salivary urea is a potential noninvasive alternative biomarker for detecting CKD.…”
Section: Introductionmentioning
confidence: 99%
“…Urea nitrogen diffuses from the blood to saliva through the salivary glands and saliva urea nitrogen (SUN) parallels blood urea nitrogen (BUN), which may be measured and used to diagnose kidney disease. [7][8][9][10][11][12][13] SUN measurement may be by standard laboratory techniques, but also by a simple dipstick method, using an SUN dipstick. [14][15][16][17][18] SUN, measured by dipstick, has been previously shown to be effective in diagnosing acute and chronic kidney disease in high-income settings, 14 15 and moreover in monitoring response to treatment.…”
Section: Bmj Global Healthmentioning
confidence: 99%